Usaha Mainan Anak Tradisional Desa Karanganyar, Kabupaten Jepara - Jayanti Putri Purwaningrum; Imaniar Purbasari; Hutomo Rusdianto (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2020)
Karanganyar Village is a village that produces traditional children's toys with toys based on coastal environmental structures. This traditional children's toy is one of Jepara's superior products that has not been developed by the Department of Industry and Trade and MSMEs in Jepara. This results in the underdevelopment of superior local products and local cultural wisdom compared to children's toy developers in other areas such as Purwakarta and Yogyakarta. The service program is a regional superior product development program in traditional children's toy producing centers, especially at Mekar Maju MSMEs. The specific objective of this program is to assist partners in developing superior local products in Karanganyar Village in the form of traditional children's toys so that they have a variety of toys with educational value and child-friendly and helping partners develop technology-based business management patterns. The main priority in this program is solutions to problems in the production process, product design, and marketing management. The results of this service activity can help MSMEs in (1) improving the business climate, (2) increasing access to productive resources, (3) developing products and marketing for MSMEs, (4) increasing the competitiveness of HR and MSMEs